2007
DOI: 10.1016/j.cellbi.2007.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a direct extracellular interaction between Met and E‐cadherin

Abstract: High levels of the Met tyrosine kinase receptor expression are associated with metastatic disease. Met activation by hepatocyte growth factor (HGF) is associated with decreased E-cadherin-dependent cell-cell contacts. The molecular mechanism underlying this process remains unclear. To better understand the relationship between E-cadherin and Met, we assessed Met localization in cells which form mature E-cadherin-dependent adhesion HT-29 and cells which have lost E-cadherin expression BT-549. Met colocalized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…E-cadherin also associates with c-Met, IGF1R and α vintegrin at the plasma membrane [39,40]. Interestingly, in the absence of α-catenin the E-cadherin/IGF1R complex does not form, suggesting that α-catenin besides its function as actin-anchoring protein also exerts a function as an important scaffolding protein.…”
Section: Epithelial Cell-cell Adhesionmentioning
confidence: 91%
“…E-cadherin also associates with c-Met, IGF1R and α vintegrin at the plasma membrane [39,40]. Interestingly, in the absence of α-catenin the E-cadherin/IGF1R complex does not form, suggesting that α-catenin besides its function as actin-anchoring protein also exerts a function as an important scaffolding protein.…”
Section: Epithelial Cell-cell Adhesionmentioning
confidence: 91%
“…In contrast, two tested G protein-coupled receptors were not regulated by Ecadherin. Indeed, several reports indicate that Ecadherin and receptor tyrosine kinases interact physically and colocalize at the lateral membranes of epithelial cells [190][191][192][193][194][195][196][197]. As for EGFR, formation of a complex with E-cadherin depended on the extracellular domain of E-cadherin [189,198], but was independent of p120ctn and b-catenin binding [189].…”
Section: Signaling Activities Of E-cadherinmentioning
confidence: 96%
“…Crosstalk occurs between MET and the developmental Wnt-b-catenin pathway in which MET directly interacts with E-cadherin and induces nuclear localization of b-catenin Apte et al 2006;Reshetnikova et al 2007). Recent work has shown that in colon cancer, HGF-producing myofibroblasts activate b-catenin-dependent transcription and stimulate cancer stem cell (CSC) populations (Vermeulen et al 2010).…”
Section: Gab1 Gab1 H G F / S F H G F / S F Hgf/sfmentioning
confidence: 99%